2017
DOI: 10.15416/ijcp.2017.6.4.240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacist Home Care on Adherence of Hypertensive Patients

Abstract: AbstrakBerdasarkan data Riset Kesehatan Dasar tahun 2013, prevalensi hipertensi mencapai 25,8%. Hipertensi dapat dikontrol dengan meminum obat secara rutin dan gaya hidup sehat. Salah satu faktor yang dapat meningkatkan keberhasilan terapi hipertensi adalah kepatuhan pasien dalam meminum obat. Home care yang dilaksanakan oleh apoteker berupa pelayanan kefarmasian yang bersifat kunjungan rumah diharapkan dapat memberikan edukasi dan pemahaman pasien terhadap terapi hipertensi sekaligus memastikan bahwa pasien t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…This was also found in a study conducted by primary healthcare units in America and Canada, where pharmacists played a role in monitoring patient medication adherence (Gums et al, 2015, Smith et al, 2016, Margolis et al, 2020. Several attempts to improve adherence to taking medication for patients with hypertension in Primary Health Centers include home pharmacy care, medication reminder tools, and pharmacist counseling (Wibowo et al, 2020, Utaminingrum et al, 2017.…”
Section: Efforts To Increase the Role Of Pharmacists In Clinical Phar...mentioning
confidence: 70%
“…This was also found in a study conducted by primary healthcare units in America and Canada, where pharmacists played a role in monitoring patient medication adherence (Gums et al, 2015, Smith et al, 2016, Margolis et al, 2020. Several attempts to improve adherence to taking medication for patients with hypertension in Primary Health Centers include home pharmacy care, medication reminder tools, and pharmacist counseling (Wibowo et al, 2020, Utaminingrum et al, 2017.…”
Section: Efforts To Increase the Role Of Pharmacists In Clinical Phar...mentioning
confidence: 70%
“…Memory decreases with age, leading to significant errors in answering the questionnaires (Utomo, 2017). However, some studies have shown that people with higher education are better able to receive information about hypertension and tend to face problems with a calmer mind (Utaminingrum et al, 2017) Based on the paired t-test in the control group before and after observation, the significance (2tailed) p = 0.093, which means p> α (0.05); therefore, it is said that there is no significant difference in the level of knowledge between the control group before and after the research. It can be concluded that without the home pharmacy care intervention, the control group before and after treatment was not significantly different.…”
Section: Table III Characteristics Of Respondents Based On Knowledge ...mentioning
confidence: 99%
“…20 Akibat paradigma berakibat pada perubahan pelayanan kefarmasian oleh apoteker seperti diperlukan adanya peningkatan pengetahuan, sikap dan keterampilan untuk lebih berinteraksi kepada pasien. 21 Terjadinya kemungkinan medication error atau kesalahan dalam pengobatan harus disadari dan dipahami oleh Apoteker saat pelayanan kefarmasian. 22 23 Menariknya pelayanan kefarmasian di rumah (home pharmacy care) belum dijalankan seutuhnya oleh para apoteker khususnya di Provinsi Lampung kekhawatiran para apoteker tersebut dipicu oleh Perkumpulan Dokter Indonesia Bersatu (PDIB) yang meminta ke Pengurus Pusat Ikatan Apoteker Indonesia (PP IAI) untuk meninjau ulang kegiatan home pharmacy care atau menurut PDIB adalah pemeriksaan kesehatan dan pengobatan dari rumah ke rumah yang dilakukan oleh oknum-oknum apoteker.…”
Section: Perlindungan Hukum Terhadap Apoteker Dalam Melakukan Praktikunclassified